Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3325/cmj.2023.64.213
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of Lebanese university students related to sexually transmitted diseases: a cross-sectional study

Vanessa Sleiman,
Sahar Obeid,
Hala Sacre
et al.

Abstract: Aim To appraise Lebanese university students’ knowledge, attitudes, and practices related to sexually transmitted diseases (STDs). Methods This cross-sectional study was conducted in March and April 2020. A total of 402 students (67.9% women) from ten universities located in different Lebanese regions were recruited through convenient sampling. Results Pursuing a major in non-health sciences compared with a major in health sciences (adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…This indicates that the level of sexual health knowledge among college students at the University of Mindanao Digos College is moderate. This result is similar to the study ofSantos et al (2016), as cited bySleiman et al (2023), which stated that students possessed a moderate level of sexual health knowledge. Cultural values appear to significantly influence the instillation of health…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that the level of sexual health knowledge among college students at the University of Mindanao Digos College is moderate. This result is similar to the study ofSantos et al (2016), as cited bySleiman et al (2023), which stated that students possessed a moderate level of sexual health knowledge. Cultural values appear to significantly influence the instillation of health…”
supporting
confidence: 91%
“…This indicates that knowledge of STD has an impact on individuals varied sexual attitude. This result is supported by the study of Sleiman et al (2023) which stated that higher knowledge scores were linked to a more positive attitude toward STDs. In addition, research indicated that increasing knowledge improved attitudes and helped young adolescents comprehend the significance of different preventive strategies.…”
Section: Regression Analysis Of Variablesmentioning
confidence: 54%